Justiça distributiva aplicada a realidade brasileira: um estudo teórico - Santos, Iranilde Gama Rodrigues dos (1990)
This work is concerned to the analysis of distributive justice application to the brazilian reality. Aiming a historical perspective of justice concepts in post and present moral and political philosophy, it shows justice is evolutionary process regarding its formation and basis, and the introduction of distributive justice focus to social psychology. Im doing so theoretical and field works of Brazilian social psychologists have been analised and compared with those of other countries looking for similarity in the distributive justice application rules. As shown in the conclusion of this work it is necessary a strong sistematic actuation of Brasilian social psychology on the subject, to cover the lack of theoretical and field research facing our reality.